2022
DOI: 10.1161/circep.122.011088
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Characterization and Outcomes of Catheter Ablation of Ventricular Arrhythmias in Patients With Mitral Annular Disjunction

Abstract: Background: Mitral annular disjunction (MAD) has recently been recognized as an arrhythmogenic entity. Data on the electrophysiological substrate as well as the outcomes of catheter ablation of ventricular arrhythmias in patients with MAD is limited. Methods: Forty patients with MAD (mean age 47±15 years; 70% female) underwent catheter ablation for ventricular arrhythmias. Detailed clinical, electrocardiographic, cardiac imaging, and procedural data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…CMR is also helpful in detecting myocardial fibrosis, which can be observed in patients with MAD, providing critical information for risk stratification. 8 Importantly, fibrosis is not necessary for a patient to experience serious cardiac events, 9 as illustrated in Case 1, highlighting the complex pathophysiology of arrhythmia generation in this population.…”
Section: Discussionmentioning
confidence: 99%
“…CMR is also helpful in detecting myocardial fibrosis, which can be observed in patients with MAD, providing critical information for risk stratification. 8 Importantly, fibrosis is not necessary for a patient to experience serious cardiac events, 9 as illustrated in Case 1, highlighting the complex pathophysiology of arrhythmia generation in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is not the first choice for MAD intervention due to the disruptive nature of shock delivery and not treating MAD at the source. Catheter ablation is a more invasive measure that in one study was successful in 90% of MAD patients in eliminating premature ventricular contractions 19 . Mitral valve surgery but specifically mitral valve repair, is a promising intervention as it is reported that it is not possible to identify any MAD in almost all patients post‐surgery when using TTE 20 .…”
Section: Discussionmentioning
confidence: 99%
“…17 premature ventricular contractions. 19 Mitral valve surgery but specifically mitral valve repair, is a promising intervention as it is reported that it is not possible to identify any MAD in almost all patients postsurgery when using TTE. 20 A study has reported that 'post-surgery, MAD association with arrhythmic events persisted but VT risk after surgery did not reach significance'.…”
Section: Points Of Cautionmentioning
confidence: 99%
“…A recent study demonstrated the efficacy of CA to reduce the VA burden for patients with MVP and MAD ( 45 ). In the presence of MAD, the arrhythmogenic substrate, defined by abnormal local electrograms (low voltage, long-duration, and fractionated, isolated mid-diastolic potentials) on electro-anatomical mapping, was identified in the anterolateral mitral annulus or MAD area ( 45 ). An exhaustive list of studies reporting the results of CA for VAs for patients with MVP or MAD is presented in Table 2 .…”
Section: Introductionmentioning
confidence: 99%